Correlation between Oxygen Saturation and Hemoglobin and Hematokrit Levels in Tetralogy of Fallot Patients - Adiputri, Farhatul Inayah; Firman, Armijn; Soenggono, Arifin (Althea Medical Journal, 2016)
Background: Hemoglobin and hematocrit levels increase in Tetralogy of Fallot (TOF) but the oxygen saturation declines. Reduced hemoglobin in circulating blood as a parameter of cyanosis does not indicate rising hemoglobin due to the ânot-workingâ hemoglobins that affect the oxygen saturation. Increasing hematocrit is the result of secondary erythrocytosis caused by declining oxygen level in blood, which is related to the oxygen saturation. This study was conducted to find the correlation between oxygen saturation and hemoglobin and hematocrite levels in TOF patients.Methods: This study was undertaken at Dr. Hasan Sadikin General Hospital in the period of January 2011 to December 2012 using the cross-sectional analytic method with total sampling technique. Inclusion criteria were medical records of TOF patients diagnosed based on echocardiography that included data on oxygen saturation, hemoglobin, and hematocrite. Exclusion criteria was the history of red blood transfusion. Results: Thirty medical records of TOF patiens from Dr. Hasan Sadikin General Hospital Bandung were included in this study. Due to skewed data distribution, Spearman correlation test was used to analyze the data. There was a significant negative correlation between oxygen saturation and hematocrit level (r= -0.412; p=0.024) and insignificant correlation between oxygen saturation and hemoglobin (r=-0.329; p= 0.076).Conclusions: There is a weak negative correlation between oxygen saturation and hematocrite levels. [AMJ.2016;3(1):152â5]DOI:Â 10.15850/amj.v3n1.724